Answer:
[tex]\frac{27(sin t - 0.6 cost)}{(0.6 sint +cost)^2}[/tex]
Explanation:
From the text of the complete problem found on internet, the expression of the force is:
[tex]F=\frac{\mu W}{\mu sin t + cos t}[/tex]
The rate of change of F with respect to t can be find by calculating the derivative of F with respect to t.
First of all, let's recall the derivative of sine and cosine:
[tex]\frac{d}{dt} sin t = cos t\\\frac{d}{dt} cos t = - sin t[/tex]
We have to calculate the derivative of a composite function, of the form
[tex]\frac{k}{g(f(x))}[/tex]
Its derivative is given by
[tex]-\frac{k}{g^2(f(x))} f'(x)[/tex]
By applying this formula to our expression, we find:
[tex]F'=-\frac{\mu W}{(\mu sin t + cos t)^2} (\mu cos t - sin t) = \frac{\mu W(sin t - \mu cost)}{(\mu sint +cost)^2}[/tex]
And by substituting the given data:
W = 45 lb
[tex]\mu = 0.6[/tex]
we find:
[tex]\frac{27(sin t -0.6 cost)}{(0.6 sint +cost)^2}[/tex]